Management of chronic rhinosinusitis with nasal polyps in Samter triad by low-dose ASA desensitization or dupilumab - Bertlich, Mattis Ralf Otfried; Ihler, Friedrich; Bertlich, Ines; Weiss, Bernhard G.; Gröger, Moritz; Haubner, Frank (Medicine, 2021)
Samter triad is a chronic condition where patients suffer from intolerance to aspirin, recurring nasal polyposis and bronchial asthma. Causative treatment is often hard. Potential approaches are the daily intake of acetylsalicylic acid (ASA), shunting arachidonic acid into the lipoxygenase pathway, and a subsequent habituation to this constant inflammatory stimulus. Alternatively, the paramount interleukins 4 and 13 may be antagonized by the monoclonal antibody dupilumab. Hence, we evaluated the daily intake of 100 mg ASA and systemic dupilumab (300 mg s.c. every 2 weeks) therapy in refractory patients for its efficacy and compliance. - We conducted a retrospective chart review for the efficacy and compliance of both continuous ASA desensitization and systemic dupilumab therapy for refractory patients. - Thirty-one patients were included in this retrospective chart review, mean follow-up was 20.4 ± 15.7 months. All patients underwent ASA desensitization. Twenty-one patients had eventually discontinued therapy after 5.8 ± 4.5 months; 11 for its side effects, 12 for its inefficacy. Twenty patients developed sinunasal complaints soon thereafter. Ten patients were still undergoing desensitization (mean duration 15.3 ± 15.7 months). These patients had a higher prevalence of concomitant anti-asthmatic medication. Seventeen refractory patients underwent systemic dupilumab therapy. After 6.4 ± 2.7 months of treatment, sinunasal outcome test (68.1 ± 13.9 vs 20.1 ± 13.9) and visual analogue scales of overall complaints (8.7 ± 0.9 vs 2.2 ± 1.5) as well as endoscopic findings and olfactory function (brief smell identification test; 3.5 ± 2.6 vs 8.6 ± 2.4) all improved significantly. - A considerable number of patients with Samter triad discontinued ASA desensitization, equally for ineffectiveness or side effects. If desensitization is to be effective, special care needs to be taken in respect to concomitant anti-asthmatic medication. Dupilumab is highly effective and safe in treating refractory patients.
Gesehen am 20.12.2021